Dampak Penggunaan Bahasa Gaul di Media Sosial terhadap Kemampuan Berbahasa Indonesia Formal Generasi Digital: The Impact of Slang Use on Social Media on the Formal Indonesian Language Skills of the Digital Generation - Arisetya, Dian (Information Technology and Science(ITScience), 2025)
The development of information and communication technology has changed the digital communication landscape, particularly in the use of slang on social media. This phenomenon raises concerns about the degradation of formal Indonesian language skills among the digital generation. This study aims to analyze the impact of slang use on social media on the formal Indonesian language skills of the digital generation. This study uses a mixed-methods approach with a sequential explanatory design. The study population was social media users aged 15-25 years in Pekanbaru City, with a sample of 200 respondents selected using a purposive sampling technique. Data collection techniques included content analysis of 1,000 posts, an online questionnaire survey, in-depth interviews with 20 respondents, and a formal language proficiency test. Quantitative data were analyzed using SPSS 25, while qualitative data were analyzed using thematic analysis techniques. The results show that slang on social media can be categorized into five main forms: abbreviations/acronyms (42%), foreign language adaptations (28%), spelling modifications (18%), changes in meaning (8%), and onomatopoeia/interjections (4%). A total of 85% of respondents use slang with high frequency, with WhatsApp being the most frequently used platform (78%). The impact analysis showed that 68% of respondents still had good spelling skills, 62% could construct formal sentences correctly, and 55% used standard vocabulary in formal writing. The use of slang on social media did not significantly reduce formal language skills, but excessive use could have a negative impact. Digital slang is a natural language variation and reflects the dynamics of digital society. This study recommends a balanced approach in addressing the phenomenon of slang as part of the natural evolution of language while maintaining formal language competence.